VD_FINDINFO Décision / 2016 / 429 vom 22. April 2016 - VD Tribunal cantonal (2016)
INDEMNITÉEN GÉNÉRAL, CLASSEMENT DE LA PROCÉDURE, FRAIS JUDICIAIRES | 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH), 430 CPP (CH)